2019
DOI: 10.1111/1754-9485.12897
|View full text |Cite
|
Sign up to set email alerts
|

Temporal impact of the publication of guidelines and randomised evidence on the adoption of hypofractionated whole breast radiotherapy for early‐stage breast cancer

Abstract: Introduction: Clinical data supporting the use of hypofractionated whole breast radiotherapy (HF-WBRT) in early-stage breast cancer patients have accumulated over the last decade. Despite the availability of the published evidence, the adoption rate of HF-WBRT has been slower-than-expected. We sought to assess the temporal impact of the publication of the guidelines and randomised evidence on the practice pattern of HF-WBRT and identify clinical predictors of its utilisation. Methods: Women with early-stage br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Despite the encouraging long-term results of hypofractionated whole-breast radiotherapy, adoption in clinical practice has been slow, as shown by several population-based analysis from the United States and Australia [15][16][17][18]. Adoption of hypofractionated radiotherapy increased over time in all of the datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the encouraging long-term results of hypofractionated whole-breast radiotherapy, adoption in clinical practice has been slow, as shown by several population-based analysis from the United States and Australia [15][16][17][18]. Adoption of hypofractionated radiotherapy increased over time in all of the datasets.…”
Section: Discussionmentioning
confidence: 99%
“…32 In Canberra (Australian Capital Territory), the use of hypofractionation for breast cancer increased from 12.1% in 2008 to 56.6% in 2016. 33 The uptake of hypofractionation in Victoria was 52% for the period 2012-2017. 34 In the USA uptake was even lower with figures less than 20% reported between 2008 and 2013.…”
Section: Palliativementioning
confidence: 99%
“…A recent report by Cancer Institute NSW indicated that across public facilities in NSW, hypofractionation was the most common radiotherapy treatment used for early‑stage breast cancer, with 73% (range 29%–97%) of patients receiving this treatment between 2015 and 2018 32 . In Canberra (Australian Capital Territory), the use of hypofractionation for breast cancer increased from 12.1% in 2008 to 56.6% in 2016 33 . The uptake of hypofractionation in Victoria was 52% for the period 2012–2017 34 .…”
Section: Adoption Of Hypofractionationmentioning
confidence: 99%
“…Whilst there have been several Australian population‐based studies reporting on adoption of HFRT following breast‐conserving surgery, 17,22–24 none has evaluated the use of post‐mastectomy HFRT. Therefore, the aim of this study was to evaluate the changing trend of post‐mastectomy HFRT over time in a population‐based cohort of women with breast cancer, and to identify factors associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the 2016 UK Royal College of Radiologists consensus statement, the use of post-mastectomy HFRT of 40 Gy in 15 fractions is recommended, 20 and in the most recent updated consensus statement in 2021, the use of postmastectomy chest wall HFRT of 26 Gy in 5 fractions is strongly recommended. 21 Whilst there have been several Australian populationbased studies reporting on adoption of HFRT following breast-conserving surgery, 17,[22][23][24] none has evaluated the use of post-mastectomy HFRT. Therefore, the aim of this study was to evaluate the changing trend of postmastectomy HFRT over time in a population-based cohort of women with breast cancer, and to identify factors associated with it.…”
Section: Introductionmentioning
confidence: 99%